Seedbank and Field Emergence of Weeds in Glyphosate-Resistant Cropping Systems in the United States. Issue 2 (June 2015) - Schwartz, Lauren M.; Gibson, David J.; Gage, Karla L.; Matthews, Joseph L.; Jordan, David L.; Owen, Micheal D. K.; Shaw, David R.; Weller, Stephen C.; Wilson, Robert G.; Young, Bryan G.
Abstract : A segment of the debate surrounding the commercialization and use of glyphosate-resistant (GR) crops focuses on the theory that the implementation of these traits is an extension of the intensification of agriculture that will further erode the biodiversity of agricultural landscapes. A large field-scale study was initiated in 2006 in the United States on 156 different field sites with a minimum 3-yr history of GR-corn, -cotton or -soybean in the cropping system. The impact of cropping system, crop rotation, frequency of using the GR crop trait, and several categorical variables on seedbank weed population density and diversity was analyzed. The parameters of total weed population density of all species in the seedbank, species richness, Shannon's H′ and evenness were not affected by any management treatment. The similarity between the seedbank and aboveground weed community was more strongly related to location than management; previous year's crops and cropping systems were also important while GR trait rotation was not. The composition of the weed flora was more strongly related to location (geography) than any other parameter. The diversity of weed flora in agricultural sites with a history of GR crop production can be influenced by several factors relating to the specific method in which the GR trait is integrated (cropping system, crop rotation, GR trait rotation), the specific weed species, and the geographical location. Continuous GR crop, compared to fields with other cropping systems, only had greater species diversity (species richness) of some life forms, i.e., biennials, winter annuals, and prostrate weeds. Overall diversity was related to geography and not cropping system. These results justify further research to clarify the complexities of crops grown with herbicide-resistance traits to provide a more complete characterization of their culture and local adaptation to the weed seedbank.